Regulation of polyamine metabolism in Pyropia cinnamomea (W.A. Nelson), an important mechanism for reducing UV‐B‐induced oxidative damage. Issue 2 (15th March 2014) - Schweikert, Katja; Hurd, Catriona L.; Sutherland, Judith E.; Burritt, David J.; Bassi, R.
<x xml:space="preserve">Abstract</x> It is generally accepted that ultraviolet (UV) radiation can have adverse affects on phototrophic organisms, independent of ozone depletion. The red intertidal seaweed Pyropia cinnamomea W.A. Nelson (previously Porphyra cinnamomea Sutherland et al. 2011), similar to many other intertidal macrophytes, is exposed to high levels of UV radiation on a daily basis due to emersion in the upper littoral zone. It has been shown that seaweeds, like higher plants, respond to an increased activity of antioxidative enzymes when exposed to stress. However, earlier investigations have shown that P. cinnamomea also compensates for stress due to UV radiation by increasing polyamine (PA) levels, especially bound‐soluble and bound‐insoluble PAs. The PA precursor putrescine (PUT) can be synthesized via two enzymatic pathways: arginine decarboxylase (ADC) and ornithine decarboxylase (ODC). Both of these enzymes showed increased activity in P. cinnamomea under UV stress. In higher plants, ADC is the enzyme responsible for increased PA levels during stress exposure, while ODC is correlated with cell division and reproduction. However, there are contrary findings in the literature. Using two irreversible inhibitors, we identified the enzyme most likely responsible for increased PUT synthesis and therefore increased stress tolerance in P. cinnamomea. Our results show that changes in the PA synthesis pathway in P. cinnamomea under UV stress are based on an increased activity of ADC. When either inhibitor was added, lipid hydroperoxide levels increased even under photosynthetically active radiation, suggesting that PAs are involved in protection mechanisms under normal light conditions as well. We also show that under optimum or low‐stress conditions, ODC activity is correlated with PUT synthesis.